Effects of Scaffolding Teaching Strategy on Students’ Performance in Chemistry in Secondary Schools in Ondo State, Nigeria - OMONIYI, ADESOJI OLUBUNMI; Ese, Torru Tessy (Advances in Social Sciences Research Journal, 2018)
The study identified Addition Reaction of Unsaturated Organic Compounds in ordinary Level West African Secondary School Certificate (WASSC) Chemistry syllabus, and examined the effects of scaffolding teaching strategy on students’ performance in chemistry. The study adopted pre-test post-test experimental design with lecture method as the control group. The sample consisted of 77 participants selected from two Senior Secondary School II Students in Akoko North East Local Government Area of Ondo State. Two intact classes were classified into experimental group Scaffolding (SF=42) and control group, lecture method (LM=35). A 20 item instrument tagged Addition Reaction of Unsaturated Hydrocarbon Achievement Test (ARUHAT) was developed by the researcher and ascertained for reliability (r=0.78, p<0.05). The study was guided by two hypotheses. Data collected were analysed using t-test. The result showed that there was a significant difference in the effectiveness of SF and students’ performance in chemistry ( t=0.043), p<0.05. Furthermore, SF was found to be more effective (X=13.01 ) than lecture method (X =10.43). The study concluded that scaffolding is an effective method of teaching chemistry concepts in general and concepts involving building of models in particular. Keywords: Scaffolding, students’ performance, effects, teaching strategy.